MXene membrane as well as preparation method and application thereof
By modifying and modifying the MXene material surface and combining it with heat shrinkable sheets, an oxidation resistance and high temperature resistance MXene film electrode was prepared, which solved the problem of poor oxidation and bonding of MXene material and improved the adsorption rate and capacity of CDI.
Patent Information
- Application Number
- CN202311194753.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-18
AI Technical Summary
MXene materials are prone to oxidation in aqueous solutions or air, which limits their long-term storage and commercial applications in CDI, and in the prior art, the MXene film and matrix materials have poor bonding properties.
MXene film electrodes with oxidation resistance and high temperature resistance are improved by surface modification, and combined with heat shrink sheets to prepare MXene membrane electrodes with oxidation resistance and high temperature resistance.
The adsorption rate and capacity of MXene membrane electrodes in CDI are improved, enhancing their stability in long-term storage and commercial applications.
Smart Images

Figure CN119637876A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of MXene material technology, and relates to an MXene film, its preparation method and application. Background Technology
[0002] MXene is a cutting-edge two-dimensional material, consisting of transition metal carbides and / or nitrides, with the general structural formula M. n+ 1X n T x Where M represents a transition metal, X represents carbon and / or nitrogen, and T represents a transition metal. x Representing end groups (e.g., -O, -OH, -F), these materials possess excellent properties such as good conductivity, high mechanical strength, and layered structure, and are considered the most promising electromagnetic shielding materials. They have broad application prospects in many technical fields. For example, CN 116621174A discloses an application of MXene two-dimensional material, proposing the application of MXene two-dimensional material, which is processed into ultrafine lines or ultrathin films for the fabrication of wireless microdevices or power supplies.
[0003] CDI is a new type of water treatment technology. Its principle is that under the action of electric field force, charged ions in the influent move towards the electrode with opposite charge. This technology can separate negatively charged ions from positively charged ions. MXene materials have good application potential in CDI (capacitive deionization) technology and can effectively remove pollutants and salts. For example, CN113881040A discloses a preparation method and application of a two-dimensional MXene / polydopamine composite desalination electrode material. The preparation method includes the following steps: (1) Block polymer self-assembly: using polyethylene oxide-block-polypropylene oxide-block-polyethylene oxide PEO 20 -b-PPO 70 -b-PEO 20 Triblock polymers self-assemble in solution to form columnar micelles as mesoporous soft templates; (2) Preparation of columnar mesoporous MXene / polydopamine two-dimensional composite nanosheets mPDA / MXene. Through the above preparation, P123 is used as a soft template to introduce mesoporous channels to both sides of MXene, so that the material has a larger internal active specific surface area and ion transport channels, which is expected to improve electrochemical performance and make it have the application prospect of capacitive deionization.
[0004] However, MXene is easily oxidized in aqueous solutions or air, limiting its long-term storage and commercial application in CDI. Furthermore, its application in CDI requires the preparation of MXene films, but existing methods for preparing MXene films exhibit poor adhesion to the substrate material. For example, CN 115569530A discloses an evaporation-driven method for preparing blended nanocomposite films, comprising the following steps: preparing a mixed dispersion containing at least two micro / nanomaterials, including MXene; placing a support film with multiple pores on the surface of the mixed dispersion, the pore diameter being larger than the solvent molecule diameter and smaller than the particle diameter of each micro / nanomaterial; heating the mixed dispersion while the support film and the mixed dispersion are in a static state, causing the micro / nanomaterials to self-assemble on the lower surface of the support film to form a blended composite self-assembled structure; and drying the blended composite self-assembled structure to obtain a blended composite film. This blended film is formed through self-assembly, resulting in poor adhesion between the material and the support film.
[0005] Based on the above research, there is a need to provide an MXene membrane that has excellent antioxidant properties, can withstand high temperatures, and has abundant ion transfer channels and adsorption sites, making it applicable to CDI technology. Summary of the Invention
[0006] The purpose of this invention is to provide an MXene membrane, its preparation method and application, and particularly to an MXene membrane electrode for CDI, its preparation method and application. The MXene membrane is modified by surface modification to improve its antioxidant and high-temperature resistance properties. When combined with heat-shrinkable sheet, a membrane electrode with antioxidant and high-temperature resistance is obtained, thereby improving the adsorption rate and capacity of CDI.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a method for preparing an MXene membrane, the method comprising the following steps:
[0009] (1) The antioxidant modified MXene material was used to form a film to obtain an initial film;
[0010] (2) After the heat-shrinkable sheet is combined with the initial film described in step (1) and heated, the MXene film is obtained.
[0011] This invention modifies MXene materials to enhance their antioxidant properties, enabling practical applications, and also improves their high-temperature tolerance, allowing for composite film formation with heat-shrink sheets to obtain micro / nano-wrinkled MXene films. Specifically, heat-shrink sheets shrink upon heating. By combining the initial film with the heat-shrink sheet and then heating, the MXene film undergoes wrinkling, resulting in a micro / nano-wrinkled MXene film. This not only increases the material loading per unit area but also provides abundant ion transfer channels and adsorption sites, thereby improving the adsorption rate and capacity of CDI.
[0012] The MXene material mentioned in this invention refers to titanium carbide MXene material, with the molecular formula Ti3C2T. x .
[0013] Preferably, the heat shrink sheet in step (2) includes any one of polystyrene heat shrink sheet, polyethylene heat shrink sheet, polylactic acid heat shrink sheet, polypropylene heat shrink sheet, polyolefin heat shrink sheet, polyester heat shrink sheet, polyvinyl chloride heat shrink sheet, copolyester heat shrink sheet or polyethylene-polyvinyl acetate heat shrink sheet.
[0014] The heat shrink sheet also includes oriented polystyrene heat shrink sheet.
[0015] Preferably, the heat shrink sheet described in step (2) is pretreated with oxygen plasma before being laminated with and heated with the initial film described in step (1).
[0016] This invention pre-treats the heat shrink sheet with oxygen plasma, which removes foreign contaminants from the surface of the heat shrink sheet and improves its hydrophilicity, thus facilitating its bonding with MXene materials.
[0017] Preferably, the oxygen plasma pretreatment conditions are an output power of 5-40 watts, for example, 5 watts, 15 watts, 25 watts, 35 watts or 40 watts, and a time of 0.5-10 minutes, for example, 0.5 minutes, 2 minutes, 5 minutes or 10 minutes, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0018] Preferably, the thickness of the heat shrink sheet in step (2) is 0.1-0.5 mm, for example, it can be 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm or 0.5 mm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0019] The thickness of the heat shrink sheet of this invention affects the degree of wrinkling of the resulting MXene film, thereby affecting the material load per unit area. Therefore, the thickness of the heat shrink sheet of this invention is within a reasonable range, which can ensure that the degree of wrinkling of the MXene film is more reasonable, so that it can achieve better performance when applied to CDI.
[0020] Preferably, the heating temperature in step (2) is 130-180°C, for example, it can be 130°C, 150°C, 170°C or 180°C, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0021] Preferably, the heating time in step (2) is 3-20 min, for example, it can be 3 min, 5 min, 7 min, 9 min, 11 min, 13 min, 15 min or 20 min, but is not limited to the listed values. Other unlisted values within the range are also applicable, preferably 5-15 min.
[0022] The heating temperature and time of this invention also affect the degree of wrinkling of the MXene membrane. Therefore, heating time and temperature within a reasonable range can further improve the performance of the MXene membrane after CDI application.
[0023] Preferably, the membrane preparation method in step (1) includes: preparing an antioxidant modified MXene material into an MXene dispersion, then performing vacuum filtration to obtain an initial membrane on filter paper.
[0024] Preferably, the pore size of the filter paper is 0.15-0.25μm, for example, it can be 0.15μm, 0.20μm or 0.25μm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0025] Preferably, the thickness of the initial film in step (1) is 0.5-3.0 μm, for example, it can be 0.5 μm, 1 μm, 1.5 μm, 2.0 μm, 2.5 μm or 3.0 μm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0026] Preferably, the antioxidant used in step (1) for antioxidant modification includes ascorbate.
[0027] Preferably, the ascorbate salt comprises sodium ascorbate.
[0028] Because some methods for preparing antioxidant MXene fail to retain the functional groups on the MXene surface, or may severely affect the electrochemical properties of MXene, causing it to lose some of its excellent performance, this invention utilizes SA (sodium ascorbate) to modify the surface of MXene. Ascorbate ions can interact with titanium atoms through hydrogen bonds and coordination bonds, protecting the titanium atoms through a capping effect. This effectively preserves the original functional groups on the MXene surface without significantly affecting the electrochemical properties of MXene. Therefore, the antioxidant MXene prepared by this method exhibits good conductivity and can be used as an electrode material for CDI technology. Furthermore, SA is a low-cost pharmaceutical product, reducing the preparation cost.
[0029] Preferably, the method for antioxidant modification of the MXene material in step (1) includes: mixing and dispersing the dispersion of the MXene material with an ascorbate solution to obtain an MXene dispersion.
[0030] Preferably, the concentration of the ascorbate solution is 10-14 mmol / L, for example, it can be 10 mmol / L, 12 mmol / L or 14 mmol / L, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0031] Preferably, the mixing and dispersion is carried out in an inert gas, and the mixing and dispersion includes sequential stirring and ultrasonic dispersion.
[0032] Preferably, the stirring and ultrasonic dispersion times are each independently 0.5-1.5 h, for example, 0.5 h, 1.0 h or 1.5 h, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0033] Preferably, the method for preparing the MXene material in step (1) includes the following steps:
[0034] MAX powder, LiF and hydrochloric acid are mixed, separated into solid and liquid components and washed to obtain a solid product. The solid product is then dispersed in water, followed by ice-water bath dispersion and centrifugation. The supernatant is retained to obtain a dispersion of MXene material.
[0035] This invention removes impurity ions from the solid product through washing, and then disperses the solid product in an ice-water bath to fully exfoliate the product, thereby obtaining a dispersion of MXene nanosheets. The ice-water bath dispersion process achieves exfoliation while avoiding oxidation of the MXene material due to excessive temperature or exposure to air. Furthermore, the two-dimensional MXene material obtained by ice-water bath dispersion is dispersed in the upper liquid after centrifugation, while the material that was not successfully exfoliated is in the lower solid layer after centrifugation.
[0036] Preferably, the ice-water bath dispersion treatment includes ultrasonic dispersion treatment in an inert atmosphere and an ice-water bath.
[0037] Preferably, the solid-liquid separation method includes centrifugal separation.
[0038] Preferably, the washing process includes first centrifugal cleaning with hydrochloric acid, and then centrifugal cleaning with deionized water.
[0039] This invention first uses hydrochloric acid for centrifugal cleaning, retaining the lower solid layer, and then washes the solid multiple times with water to thoroughly wash away the residual hydrochloric acid solution and other ions in the product, thereby removing impurity ions.
[0040] Preferably, the centrifugal cleaning speed is 3000-8000 rpm, for example, it can be 3000 rpm, 5000 rpm or 8000 rpm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0041] Preferably, after the washing process, the pH of the upper solution after the solid product is mixed with water is ≥6, for example, it can be 6, 6.5 or 7, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0042] As a preferred embodiment of the method for preparing the MXene membrane according to the present invention, the method includes the following steps:
[0043] (1) Mix MAX powder, LiF and hydrochloric acid, separate solid and liquid, centrifuge and wash with hydrochloric acid and centrifuge with deionized water to obtain a solid product. Then disperse the solid product with water, and then perform ultrasonic dispersion treatment in an inert atmosphere and ice water bath. Finally, centrifuge and separate the upper liquid after centrifugation to obtain a dispersion of MXene material.
[0044] (2) The sodium ascorbate solution and the dispersion of MXene material described in step (1) are stirred and ultrasonically dispersed in an inert gas to obtain an MXene dispersion.
[0045] The concentration of the sodium ascorbate solution is 10-14 mmol / L;
[0046] (3) The MXene dispersion obtained in step (2) is filtered to obtain an initial film with a thickness of 0.5-3.0 μm on filter paper with a pore size of 0.15-0.25 μm;
[0047] (4) Transfer the initial film described in step (3) onto a heat shrink sheet, and then heat it at 130-180°C for 5-15 minutes to obtain the MXene film;
[0048] The thickness of the heat shrink sheet is 0.1-0.5 mm. Before use, the heat shrink sheet is pretreated with oxygen plasma.
[0049] In a second aspect, the present invention provides an MXene membrane, which is prepared by the preparation method described in the first aspect.
[0050] Thirdly, the present invention provides a CDI device comprising the MXene membrane as described in the second aspect.
[0051] Preferably, the ion adsorption capacity of the MXene membrane is 94.7-210.1 mg / g, for example, it can be 95 mg / g, 100 mg / g, 150 mg / g or 200 mg / g, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0052] The present invention achieves an ion adsorption capacity of 94.67-210.06 mg / g for sodium chloride solution using the MXene membrane under different voltages.
[0053] Preferably, the MXene membrane serves as both the cathode and anode of a CDI device.
[0054] Preferably, the water flow pattern of the CDI device is bottom inlet and top outlet.
[0055] The CDI device of this invention uses a bottom-in, top-out water flow method, which can improve the separation effect.
[0056] Preferably, the voltage applied to the CDI device is 1-1.7V, for example, it can be 1V, 1.2V, 1.4V, 1.6V or 1.7V, but is not limited to the listed values. Other unlisted values within the range are also applicable. Preferably, it is 1.5-1.7V, and more preferably 1.6V.
[0057] The MXene membrane described in this invention, when used in a CDI device as both a cathode and anode, exhibits the highest ion adsorption capacity when the voltage applied to the CDI device is 1.6V.
[0058] Compared with the prior art, the present invention has the following beneficial effects:
[0059] This invention utilizes heat-shrinkable sheets to prepare antioxidant MXene wrinkled electrodes for CDI applications. On the one hand, the antioxidant properties can slow down the oxidation process of the MXene electrode during preparation and testing. On the other hand, the increased interlayer spacing of MXene due to antioxidant intercalation and the abundant pores brought by the wrinkles are conducive to the transfer and adsorption of ions in water on the electrode surface. These two aspects interact and work together to improve the CDI adsorption capacity and rate. Attached Figure Description
[0060] Figure 1 This is a flowchart of the synthesis and modification of the MXene material described in Embodiment 1 of the present invention in steps (1) and (2);
[0061] Figure 2 The TEM image of the antioxidant-modified MXene material described in Example 1 of this invention;
[0062] Figure 3 This is a SEM image of the MXene membrane described in Embodiment 1 of the present invention;
[0063] Figure 4 The graph shows the change in solution conductivity when the MXene membrane described in Example 1 and Comparative Example 1 of this invention is applied in CDI with an applied voltage of 1.4V to adsorb a 750 mg / L sodium chloride solution.
[0064] Figure 5 The bar chart shows the ion adsorption degree when the MXene membrane described in Example 1 and Comparative Example 1 of this invention is applied in CDI with different applied voltages.
[0065] Figure 6 The bar chart shows the ion adsorption degree when the MXene membrane described in Example 1 and Comparative Example 1 of this invention is applied in CDI with different conductivity.
[0066] Figure 7 The XPS full spectrum analysis spectra of the MXene material with antioxidant modification as described in Example 1 of this invention and the MXene material without antioxidant modification in Comparative Example 1 are shown.
[0067] Figure 8 This is a high-resolution XPS spectrum of the C1s region of the MXene material after antioxidant modification as described in Example 1 of this invention;
[0068] Figure 9 This is a high-resolution XPS spectrum of the C1s region of the MXene material without antioxidant modification as described in Comparative Example 1 of this invention.
[0069] Figure 10 The images show the XRD patterns of the MXene material with antioxidant modification described in Example 1 of this invention, the MXene material without antioxidant modification described in Comparative Example 1, and the MXene material with antioxidant modification described in Example 1, after being soaked in hydrochloric acid. Detailed Implementation
[0070] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0071] Example 1
[0072] This embodiment provides a method for preparing an MXene membrane, the method comprising the following steps:
[0073] (1) 1g MAX powder, 3g LiF and 40mL of 9mol / L hydrochloric acid were stirred at 35℃ at 400 rpm for 24 hours, then centrifuged at 3000 rpm for 5 minutes and the lower solid product was retained. The lower solid product was centrifuged at 3000 rpm for 5 minutes with 2mol / L hydrochloric acid solution, then centrifuged at 3000 rpm for 5 minutes with deionized water, and then centrifuged at 8000 rpm for 5 minutes with deionized water. After each centrifugation, the supernatant was removed and deionized water was added again until the pH of the supernatant solution reached 6. The washed solid product was dispersed with deionized water and then ultrasonically dispersed in an argon atmosphere and an ice-water bath for 1 hour. Finally, it was centrifuged at 3000 rpm for 20 minutes. After centrifugation, the supernatant was retained to obtain the dispersion of MXene material.
[0074] (2) 30 mL of sodium ascorbate solution (SA solution) with a concentration of 12 mmol / L and the dispersion of MXene material obtained in step (1) were stirred at 400 rpm for 1 hour in argon atmosphere, and then ultrasonically dispersed for 30 min to obtain MXene dispersion. This achieved antioxidant modification of MXene material, resulting in antioxidant modified MXene material (SA-MXene). The TEM image of the antioxidant modified MXene material is shown below. Figure 2 As shown, the XPS full spectrum analysis spectrum is as follows: Figure 7 As shown, the high-resolution XPS spectrum of the C 1s region is as follows: Figure 8 As described above, the XRD pattern is as follows: Figure 10 As shown, the XRD pattern of the MXene material after being soaked in 2 mol / L hydrochloric acid for 2 min, then washed with deionized water and dried is shown in the figure. Figure 10 As shown;
[0075] The flowcharts for the synthesis and modification of the MXene material in steps (1) and (2) are as follows: Figure 1 As shown;
[0076] (3) The MXene dispersion obtained in step (2) was filtered by using filter paper with a pore size of 0.22 μm and a radius of 47 mm to obtain an initial film with a thickness of 1 μm on the filter paper;
[0077] (4) Transfer the initial film obtained in step (3) onto a polystyrene heat-shrink sheet, and then heat it at 160°C for 8 minutes to obtain the MXene film. The SEM image of the MXene film is shown below. Figure 3 As shown, the MXene membrane is used in CDI. When a voltage of 1.4V is applied, it adsorbs a 750 mg / L sodium chloride solution. The change in solution conductivity is shown in the graph. Figure 4 As shown in the bar chart, the ion adsorption degree is displayed under different applied voltages. Figure 5 As shown in the bar chart, the degree of ion adsorption at different conductivity levels is as follows: Figure 6 As shown;
[0078] The polystyrene heat shrink sheet has a thickness of 0.3 mm. Before use, the polystyrene heat shrink sheet is pretreated with oxygen plasma at an output power of 10 watts for 5 minutes.
[0079] Example 2
[0080] This embodiment provides a method for preparing an MXene membrane, the method comprising the following steps:
[0081] (1) 1g MAX powder, 3g LiF and 40mL of 9mol / L hydrochloric acid were stirred at 35℃ at 400 rpm for 24 hours. Then, the mixture was centrifuged at 3000 rpm for 5 minutes and the lower solid product was retained. The mixture was then centrifuged at 3000 rpm for 5 minutes with 2mol / L hydrochloric acid solution and the lower solid product was retained. The mixture was then centrifuged at 3000 rpm for 5 minutes with deionized water and the lower solid product was retained. The mixture was then centrifuged at 8000 rpm for 5 minutes with deionized water. After each centrifugation, the supernatant was removed and deionized water was added again until the pH of the supernatant solution reached 6. The washed solid product was dispersed with deionized water and then ultrasonically dispersed in an argon atmosphere and an ice-water bath for 1 hour. Finally, the mixture was centrifuged at 3000 rpm for 20 minutes. After centrifugation, the supernatant was retained to obtain the dispersion of MXene material.
[0082] (2) 30 mL of sodium ascorbate solution with a concentration of 10 mmol / L and the dispersion of MXene material described in step (1) were stirred in argon gas at a speed of 400 rpm for 1 hour, and then ultrasonically dispersed for 30 min to obtain MXene dispersion, thereby realizing the antioxidant modification of MXene material and obtaining antioxidant modified MXene material.
[0083] (3) The MXene dispersion obtained in step (2) was filtered by using filter paper with a pore size of 0.25 μm and a radius of 47 mm to obtain an initial film with a thickness of 3 μm on the filter paper.
[0084] (4) Transfer the initial film described in step (3) onto a polystyrene heat shrink sheet, and then heat it at 180°C for 5 minutes to obtain the MXene film;
[0085] The polystyrene heat shrink sheet has a thickness of 0.5 mm. Before use, the polystyrene heat shrink sheet is pretreated with oxygen plasma at an output power of 40 watts for 0.5 min.
[0086] Example 3
[0087] This embodiment provides a method for preparing an MXene membrane, the method comprising the following steps:
[0088] (1) 1g MAX powder, 3g LiF and 40mL of 9mol / L hydrochloric acid were stirred at 35℃ at 400 rpm for 24 hours. Then, the mixture was centrifuged at 3000 rpm for 5 minutes and the lower solid product was retained. The mixture was then centrifuged at 3000 rpm for 5 minutes with 2mol / L hydrochloric acid solution and the lower solid product was retained. The mixture was then centrifuged at 3000 rpm for 5 minutes with deionized water and the lower solid product was retained. The mixture was then centrifuged at 8000 rpm for 5 minutes with deionized water. After each centrifugation, the supernatant was removed and deionized water was added again until the pH of the supernatant solution reached 6. The washed solid product was dispersed with deionized water and then ultrasonically dispersed in an argon atmosphere and an ice-water bath for 1 hour. Finally, the mixture was centrifuged at 3000 rpm for 20 minutes. After centrifugation, the supernatant was retained to obtain the dispersion of MXene material.
[0089] (2) 30 mL of sodium ascorbate solution with a concentration of 14 mmol / L and the dispersion of MXene material described in step (1) were stirred in argon gas at a speed of 400 rpm for 1 hour, and then ultrasonically dispersed for 30 min to obtain MXene dispersion, thereby realizing the antioxidant modification of MXene material and obtaining antioxidant modified MXene material.
[0090] (3) The MXene dispersion obtained in step (2) was filtered by using filter paper with a pore size of 0.15 μm and a radius of 47 mm to obtain an initial film with a thickness of 0.5 μm on the filter paper;
[0091] (4) Transfer the initial film described in step (3) onto a polystyrene heat shrink sheet, and then heat it at 130°C for 15 min to obtain the MXene film;
[0092] The polystyrene heat shrink sheet has a thickness of 0.1 mm. Before use, the polystyrene heat shrink sheet is pretreated with oxygen plasma at an output power of 5 watts for 10 minutes.
[0093] Example 4
[0094] This embodiment provides a method for preparing an MXene membrane. Except for the heating time of 3 minutes in step (4), the preparation method is the same as that in Example 1.
[0095] Example 5
[0096] This embodiment provides a method for preparing an MXene membrane. Except for the heating time of 20 min in step (4), the preparation method is the same as that in Example 1.
[0097] Example 6
[0098] This embodiment provides a method for preparing an MXene membrane. Except for step (4), in which the polystyrene heat shrink sheet is not pretreated with oxygen plasma before use, the preparation method is the same as in Example 1.
[0099] Example 7
[0100] This embodiment provides a method for preparing an MXene film. Except for the polystyrene heat shrink sheet in step (4) having a thickness of 0.05 mm, the preparation method is the same as in Example 1.
[0101] Example 8
[0102] This embodiment provides a method for preparing an MXene film. Except for the polystyrene heat shrink sheet in step (4) having a thickness of 0.6 mm, the preparation method is the same as in Example 1.
[0103] Example 9
[0104] This embodiment provides a method for preparing an MXene membrane. Except for the initial membrane thickness of 0.1 μm in step (3), the preparation method is the same as in Example 1.
[0105] Example 10
[0106] This embodiment provides a method for preparing an MXene membrane. Except for the initial membrane thickness of 4 μm mentioned in step (3), the preparation method is the same as that in Example 1.
[0107] Comparative Example 1
[0108] This comparative example provides a method for preparing an MXene film. The preparation method is the same as in Example 1 except that step (2) is not performed and the MXene material without antioxidant modification is used for film preparation.
[0109] The XPS full spectrum analysis spectrum of the MXene material without antioxidant modification is as follows: Figure 7 As shown, the high-resolution XPS spectrum of the C1s region is as follows: Figure 9 As shown, the XRD pattern is as follows Figure 10 As shown;
[0110] The MXene membrane was used in CDI (Continuous Dioxide) with an applied voltage of 1.4V to adsorb sodium chloride solution of 750 mg / L. The change in solution conductivity is shown in the graph below. Figure 4 As shown in the bar chart, the ion adsorption degree is displayed under different applied voltages. Figure 5 As shown in the figure, the bar chart of ion adsorption degree at different conductivity is as follows: Figure 6 As shown;
[0111] Comparative Example 2
[0112] This comparative example provides a method for preparing an MXene membrane. The preparation method is the same as in Example 1 except that steps (3) and (4) are omitted, and instead a supporting membrane is added to the MXene dispersion in step (2) and then subjected to static heating to form a membrane. The supporting membrane is a polypropylene membrane, and the heating temperature is 80°C for 50 minutes.
[0113] Comparative Example 3
[0114] This comparative example provides a method for preparing an MXene membrane. The preparation method is the same as in Example 1 except that step (4) is omitted and the initial membrane obtained in step (3) is used directly as the MXene membrane.
[0115] The MXene membranes obtained in the above embodiments and comparative examples were used as the cathode and anode of the CDI device to adsorb ions in a sodium chloride solution with a concentration of 750 mg / L (the ions in the sodium chloride solution were separated and adsorbed through adsorption and ion exchange). The water flow direction of the CDI device was bottom inlet and top outlet. Voltages of 1.0V, -1.0V, 1.2V, -1.2V, 1.4V, -1.4V, 1.6V, and 1.6V were applied to the two ends of the capacitor device, respectively. The device was run for 30 minutes at each voltage to test the difference in the adsorption effect of the device on ions in the sodium chloride solution under different voltages. When the sodium chloride solution was 750 mg / L and the voltage applied to the CDI device was 1.6V, the ion adsorption degree is shown in Table 1.
[0116] Table 1
[0117]
[0118]
[0119] As can be seen from Table 1 and the attached diagrams obtained from the tests:
[0120] (1) When different voltages are applied to the CDI device, the adsorption degree of the MXene membrane of the present invention for ions in sodium chloride solution is 94.7 mg / g-210.1 mg / g. The adsorption degree of the present invention can reach more than 210.1 mg / g when the sodium chloride solution is 750 mg / L and the voltage is 1.6V. As can be seen from Example 1 and Comparative Example 1, the antioxidant modification of the present invention enables the MXene membrane to be used in CDI and has excellent ion adsorption performance. As can be seen from Example 1 and Comparative Example 2, Comparative Example 2 adopts the conventional deposition self-assembly film preparation method. The bonding strength between the MXene material and the support film is poor and the wrinkled structure of the present invention cannot be obtained. Therefore, the performance of the MXene membrane in CDI is greatly reduced. As can be seen from Example 1 and Comparative Example 3, the present invention combines the initial membrane with the heat shrink sheet to obtain a micro-nano wrinkled MXene membrane, which, together with the antioxidant modification, greatly improves the performance of the MXene membrane.
[0121] (2) As can be seen from Examples 1 and 4-5, the heating time when the initial film and heat shrink sheet are composited in this invention will affect the degree of wrinkling of the MXene film, thereby affecting the adsorption performance. As can be seen from Examples 1 and 6, the oxygen plasma pretreatment of the heat shrink sheet in this invention can improve the bonding strength between the heat shrink sheet and the initial film, thereby improving the performance of the final MXene film. As can be seen from Examples 1 and 7-10, the thickness of the initial film and the heat shrink sheet in this invention will also affect the degree of wrinkling and performance of the MXene film.
[0122] (3) By the present invention Figure 3 It can be seen that the present invention can obtain MXene films with micro-nano wrinkled structures; from Figure 7 and Figure 8 It can be seen that sodium and carbon-oxygen double bonds are present in the modified MXene membrane, confirming the presence of sodium ascorbate; Figure 10 It can be seen that the 2θ angle of the (002) lattice plane of MXene after antioxidant modification decreases, which confirms that the intercalation effect of sodium ascorbate increases the interlayer spacing of MXene material. Compared with the modified MXene, the 2θ angle of the (002) lattice plane of the modified MXene after soaking in hydrochloric acid increases and is almost the same as the 2θ angle of the (002) lattice plane of MXene, which confirms that the sodium ascorbate intercalation can be washed away by hydrochloric acid, so that the interlayer spacing of MXene is restored.
[0123] In summary, this invention provides an MXene membrane electrode for CDI, its preparation method, and its application. The MXene membrane is modified by surface modification to improve its antioxidant and high-temperature resistance properties. When combined with heat-shrinkable sheets, a membrane electrode with antioxidant and high-temperature resistance is obtained, thereby improving the adsorption rate and capacity of CDI.
[0124] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A method for preparing a MXene film, characterized in that: The preparation method comprises the following steps: (1) preparing a film of the antioxidant modified MXene material to obtain an initial film; (2) Compounding and heating the heat shrinkable sheet and the initial film in step (1) to obtain the MXene film.
2. The preparation method according to claim 1, characterized in that: The heat shrinkable sheet in step (2) includes any one of a polystyrene heat shrinkable sheet, a polyethylene heat shrinkable sheet, a polylactic acid heat shrinkable sheet, a polypropylene heat shrinkable sheet, a polyolefin heat shrinkable sheet, a polyester heat shrinkable sheet, a polyvinyl chloride heat shrinkable sheet, a copolyester heat shrinkable sheet or a polyethylene-polyvinyl acetate heat shrinkable sheet; Preferably, the heat shrinkable sheet in step (2) is pretreated with oxygen plasma before being compounded and heated with the initial film in step (1); Preferably, the thickness of the heat shrinkable sheet in step (2) is 0.1-0.5 mm.
3. The preparation method according to claim 1 or 2, characterized in that: The heating temperature in step (2) is 130-180° C. Preferably, the heating time in step (2) is 3-20 min, preferably 5-15 min.
4. The preparation method according to any one of claims 1 to 3, characterized in that The film-making method in step (1) comprises: preparing the antioxidant modified MXene material into a MXene dispersion, and then filtering it to obtain an initial film on filter paper; Preferably, the pore size of the filter paper is 0.15-0.25 μm; Preferably, the thickness of the initial film in step (1) is 0.5-3.0 μm.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The antioxidant used in the antioxidant modification in step (1) includes ascorbate; Preferably, the ascorbate comprises sodium ascorbate; Preferably, the method for antioxidant modification of the MXene material in step (1) comprises: mixing and dispersing a dispersion of the MXene material with an ascorbate solution to obtain a MXene dispersion; Preferably, the concentration of the ascorbate solution is 10-14 mmol / L; Preferably, the mixing and dispersing is carried out in an inert gas, and the mixing and dispersing includes stirring mixing and ultrasonic dispersing carried out in sequence; Preferably, the stirring mixing and ultrasonic dispersion times are independently 0.5-1.5 h.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The method for preparing the MXene material in step (1) comprises the following steps: The MAX powder, LiF and hydrochloric acid are mixed, solid-liquid separated and washed to obtain a solid product, and then the solid product is dispersed with water, and then ice-water bath dispersion treatment and centrifugal separation are performed, and the upper layer liquid is retained to obtain a dispersion of MXene material; Preferably, the ice-water bath dispersion treatment comprises ultrasonic dispersion treatment in an inert atmosphere and an ice-water bath; Preferably, the washing comprises firstly centrifugally washing with hydrochloric acid and then centrifugally washing with deionized water; Preferably, the rotation speed of the centrifugal washing is 3000-8000rpm; Preferably, after the solid product is washed and mixed with water, the pH of the upper solution is ≥6.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) MAX powder, LiF and hydrochloric acid are mixed, solid-liquid separated, centrifuged and washed with hydrochloric acid and deionized water to obtain a solid product, and then the solid product is dispersed with water, and then ultrasonically dispersed in an inert atmosphere and an ice water bath, and finally centrifuged, and the upper layer liquid is retained after centrifugal separation to obtain a dispersion of MXene material; (2) stirring and mixing the sodium ascorbate solution and the dispersion of the MXene material described in step (1) in an inert gas and ultrasonically dispersing the mixture to obtain a MXene dispersion; The concentration of the sodium ascorbate solution is 10-14mmoL / L; (3) filtering the MXene dispersion in step (2) to obtain an initial membrane with a thickness of 0.2-3.0 μm on filter paper with a pore size of 0.15-0.25 μm; (4) transferring the initial film of step (3) to a heat shrinkable sheet, and then heating at 130-180° C. for 5-15 min to obtain the MXene film; The thickness of the heat shrinkable sheet is 0.1-0.5 mm. Before use, the heat shrinkable sheet is pretreated with oxygen plasma.
8. A MXene film, characterized in that The MXene film is prepared by the preparation method according to any one of claims 1 to 7.
9. A CDI device, characterized in that: The CDI device comprises the MXene membrane of claim 8.
10. The CDI device according to claim 9, characterized in that: The MXene membrane is the cathode and anode of the CDI device; Preferably, the water flow mode of the CDI device is bottom-in and top-out.
Citation Information
Patent Citations
Preparation method and application of two-dimensional MXene / polydopamine composite desalination electrode material
CN113881040A
Blended nano composite film preparation method based on evaporation driving
CN115569530A
Application of MXene two-dimensional material
CN116621174A